2010
DOI: 10.1021/cm101090p
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Dealloyed PtCu3 Thin Films and Catalytic Activity for Oxygen Reduction

Abstract: The detailed structure and composition (surface and bulk) as well as catalytic activity for oxygen reduction of electrochemically dealloyed PtCu3 thin films have been investigated. Synchrotron-based anomalous X-ray diffraction (AXRD) reveals that a Pt enriched surface region (∼1.0 nm thick) and a Cu depleted interior (atomic ratio different from that of PtCu3) are formed in the dealloyed film, and we directly observe a compressive lattice strain in the Pt surface region. The dealloyed PtCu3 thin films show a ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
157
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(174 citation statements)
references
References 59 publications
14
157
0
3
Order By: Relevance
“…Dealloying by using either chemical or electrochemical methods is well known to induce perturbations in the Pt surface with other non-precious metal-depleted interiors. Strasser and co-workers also reported that electrochemically dealloyed PtCu 3 thin films have a Pt-enriched surface with perturbed thin layers that cover the Cu-depleted interior [21]. In our work, PtCu 3 /C-AT and PtCu 5 /C-AT showed the same fcc structure when compared with Pt catalyst while the Pt lattices were deformed in the XRD results, indicating the existence of a Pt-rich PtCu alloy structure.…”
Section: Physical Properties Of Ptcu X /C-ht and Ptcu X /C-at Catalystssupporting
confidence: 64%
“…Dealloying by using either chemical or electrochemical methods is well known to induce perturbations in the Pt surface with other non-precious metal-depleted interiors. Strasser and co-workers also reported that electrochemically dealloyed PtCu 3 thin films have a Pt-enriched surface with perturbed thin layers that cover the Cu-depleted interior [21]. In our work, PtCu 3 /C-AT and PtCu 5 /C-AT showed the same fcc structure when compared with Pt catalyst while the Pt lattices were deformed in the XRD results, indicating the existence of a Pt-rich PtCu alloy structure.…”
Section: Physical Properties Of Ptcu X /C-ht and Ptcu X /C-at Catalystssupporting
confidence: 64%
“…Therefore, we may further down-select the scan rate to 20 mV/s which is fairly common in the literature. 4,[29][30][31][32][33]50 ORR activity.-Steady-state.-Practical PEMFCs are typically evaluated for performance using pseudo steady-state conditions and the question arises as to whether it is possible and reasonable to conduct similar measurements in RDE studies and identify the consequent advantages or repercussions. A schematic of the ORR protocol applied for the measurement of pseudo steady-state ORR I-V curves (15 min/point) in both the anodic and cathodic directions is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, reported enhancements in the orr activity of originally called Pt "skeleton", then "surface strained" or "core-shell type" catalysts have been assigned to a lowering of the Pt-Pt bond distance [16,17]. Electronic effects have also been suggested to be of benefit for the orr activity.…”
Section: Introductionmentioning
confidence: 97%
“…Other catalyst architectures referred to as core-shell, surface strained and Pt enriched catalysts have also been suggested [6,7,[12][13][14][15][16][17]. Increases in mass and specific orr activities of such catalysts over Pt-only catalysts have been reported.…”
Section: Introductionmentioning
confidence: 99%